Student Perception on Initial Experience of Flipped Classroom in Sport Education Department - Zen Fadli; Heri Masmur Sembiring; M. Eko Isdianto; Widya Andayani (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This study aimed to investigate the perception of students towards their initial experience with the flipped classroom model of education in Sport. Qualitative research method was employed, including the distribution of questionnaires and interviewing ten participants, consisting of university students in Sport education. The study found that a significant number of students had a positive view of the interactive and participatory nature of the flipped classroom. They appreciated the increased agency and felt more engaged in the learning process. However, some students faced initial challenges, including inadequate internet connectivity, difficulties in adapting to the flipped classroom's requirements, and inclusivity concerns. The study recommends that universities invest in robust Wi-Fi infrastructure and instructional resources to improve the overall student experience with the flipped classroom model. Additionally, universities could enhance the orientation programs to support students in transitioning to a flipped classroom model. Finally, this study proposes that further research should be undertaken to identify areas of improvement to institutions that aim to transition to the flipped classroom model of education effectively.